Exploring Teachers’ Polite Requests in Indonesian EFL Classroom Interaction - Anggreni, Afrilia; Mahmud, Murni; Halim, Abdul (Har Press Indonesia, 2023)
This essay seeks to identify the courteous requests used by instructors and the variables influencing their utilization. Two English teachers from a private school in Makassar, South Sulawesi, Indonesia, participated in this study. An interview and an audio recording were used to get the data. The two teachers' instructional strategies were observed, documented, and then analyzed. According to the research's findings, teachers prioritized requests in order of politeness. The social distance, level of power, and socioeconomic situation all had an impact on these courteous inquiries. It is anticipated that this research's findings will be informative and helpful to the teaching profession both theoretically and practically.